2010
DOI: 10.1016/j.bbadis.2010.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Celiac anti-tissue transglutaminase antibodies interfere with the uptake of alpha gliadin peptide 31–43 but not of peptide 57–68 by epithelial cells

Abstract: Celiac disease is characterized by the secretion of IgA-class autoantibodies that target tissue transglutaminase (tTG). It is now recognized that anti-tTG antibodies are functional and not mere bystanders in the pathogenesis of celiac disease. Here we report that interaction between anti-tTG antibodies and extracellular membrane-bound tTG inhibits peptide 31-43 (but not peptide 57-68) uptake by cells, thereby impairing the ability of p31-43 to drive Caco-2 cells into S-phase. This effect did not involve tTG ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 49 publications
4
37
0
Order By: Relevance
“…2C, 3). This is in agreement with Caputo et al [35] who observed a reduced endocytosis of fluorescence signals in cells incubated with labeled P31–43 but only a slightly reduced endocytosis with labeled P57–68. Schumann et al [29], however, reported the inhibition of translocation of intact fluorescence labeled P56–88 by using MβCD.…”
Section: Discussionsupporting
confidence: 93%
“…2C, 3). This is in agreement with Caputo et al [35] who observed a reduced endocytosis of fluorescence signals in cells incubated with labeled P31–43 but only a slightly reduced endocytosis with labeled P57–68. Schumann et al [29], however, reported the inhibition of translocation of intact fluorescence labeled P56–88 by using MβCD.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, some studies have highlighted the ability of anti-TG2 antibodies to direct out-in signalling in different cell models through the interaction with the membrane-bound TG2 [27], [28]. We also reported that celiac anti-TG2 antibodies were able to induce ERK phosphorylation and calcium mobilization from intracellular stores in intestinal epithelial cells [29], [30].…”
Section: Introductionmentioning
confidence: 62%
“…Antibody treatments were performed as previously described [29]. Briefly, cells were plated at 1.5×10 4 cell/cm 2 and 24 h later were cultured for 72 h in medium containing 0.1% fetal bovine serum.…”
Section: Methodsmentioning
confidence: 99%
“…Anti-tissue transglutaminase antibodies (anti-tTG), appear to be not only a diagnostic marker in celiac patients on gluten-containing diet, but also have been implicated in the pathogenesis of many CD manifestations [26,27,28], including fertility and pregnancy complications. The enzyme transglutaminase can be found in many organs, and may have a role in interactions of cells with the surrounding extracellular matrix [29], in processes of cell adhesion, migration and spreading.…”
Section: Possible Pathogenic Mechanismsmentioning
confidence: 99%